2021
DOI: 10.48550/arxiv.2101.11007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observing Invisible Axions with Gravitational Waves

Marco Gorghetto,
Edward Hardy,
Horia Nicolaescu

Abstract: If the Peccei-Quinn symmetry associated to an axion has ever been restored after inflation, axion strings inevitably produce a contribution to the stochastic gravitational wave background. Combining effective field theory analysis with numerical simulations, we show that the resulting gravitational wave spectrum has logarithmic deviations from a scale invariant form with an amplitude that is significantly enhanced at low frequencies. As a result, a single ultralight axion-like particle with a decay constant la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 154 publications
4
28
1
Order By: Relevance
“…Recently, the NANOGrav collaboration has reported the detection of a signal, which could be compatible with a stochastic GW background [19]. If this detection is confirmed in the future, it could be a manifestation of the stochastic GW background originated from the epoch around the QCD energy scale [20][21][22][23][24][25][26]. Interestingly, the source of these GWs might be the presence of primordial magnetic fields at the QCD scale [21] .…”
Section: Introductionmentioning
confidence: 92%
“…Recently, the NANOGrav collaboration has reported the detection of a signal, which could be compatible with a stochastic GW background [19]. If this detection is confirmed in the future, it could be a manifestation of the stochastic GW background originated from the epoch around the QCD energy scale [20][21][22][23][24][25][26]. Interestingly, the source of these GWs might be the presence of primordial magnetic fields at the QCD scale [21] .…”
Section: Introductionmentioning
confidence: 92%
“…The evolution of axion strings and axion radiation is governed by the classical field equations of the underlying scalar field theory, and due to their non-linearities, lattice simulations are required to go beyond order-of-magnitude estimates. In recent years, several groups have studied the evolution of axion strings and the production of axions using lattice simulations [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…We included the contribution from these high modes in this updated study, which leads to substantial modifications to the GW spectrum at low f for standard thermal history as well as at high f with the presence of an early matter domination epoch. We also discuss the consequence for the prediction of SGWB if the non-scaling behavior found in some simulation results for early evolution sustains in the late-time evolution of a global string network, compare with the results found in [46,65], and suggest potential modifications to the VOS model to accommodate such a feature. We will dive into the time-frequency correspondence for global strings, which is the guiding principle for testing standard cosmology.…”
mentioning
confidence: 71%
“…With a semianalytical approach based on the Velocity-dependent One-Scale (VOS) model, our earlier work [24] demonstrated that the GW signal from global strings, albeit notably smaller than that from its NG string counterpart, can be within reach of future GW experiments such as LISA [6,7], AEDGE [47], DECIGO and BBO [48]. Such a positive prospect of detection has been confirmed by simulation-based work [45,46], although details differ which will be addressed in this work.…”
mentioning
confidence: 79%
See 1 more Smart Citation